2015
DOI: 10.1021/acs.jproteome.5b00021
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Newly Synthesized Proteins over the Adult Life Span of Caenorhabditis elegans

Abstract: Little is known regarding how the synthesis and degradation of individual proteins changes during the life of an organism. Such knowledge is vital to understanding the aging process. To fill this knowledge gap, we monitored newly synthesized proteins on a proteome scale in Caenorhabditis elegans over time during adulthood using a SILAC-based label-chase approach. For most proteins, the rate of appearance of newly synthesized protein was high during the first 5 days of adulthood, slowed down between the fifth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
5
24
0
Order By: Relevance
“…In day 5 adult worms, average THPLH is much longer, which is in line with observations by Vukoti et al (2015). This study used a pulsed SILAC-based approach similar to ours to study protein turnover in wild-type worms during adulthood and found that protein turnover drastically dropped after day 5.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In day 5 adult worms, average THPLH is much longer, which is in line with observations by Vukoti et al (2015). This study used a pulsed SILAC-based approach similar to ours to study protein turnover in wild-type worms during adulthood and found that protein turnover drastically dropped after day 5.…”
Section: Discussionsupporting
confidence: 87%
“…For determination of THPLH by pulsed SILAC, the adult worms have the benefit that small differences in synchronization have less effect than they do in developing worms and that the total protein concentration per worm stays largely the same over the course of the experiment. However, total label incorporation is lower (Vukoti et al, 2015), which makes estimation of THPLH less reliable. Worms were pulse labeled for 6, 24, and 48 hr and harvested.…”
Section: Protein Turnover Rates In Aging Wormsmentioning
confidence: 99%
“…Decline in PEPCK activity after the reproductive peak also occurred in glp-1 mutants, validating that it is not a result of loss of eggs. The reciprocal changes in PEPCK-C and PK with age also cannot be an effect of aging-associated loss of protein homeostasis (41), which predicts declines in both. We conclude that aging involves a programmed metabolic event that includes reciprocal changes in PEPCK-C and PK.…”
Section: Aging Involves a Progressive Decline In Pepck-c And A Reciprmentioning
confidence: 99%
“…In recent years, proteomics analyses have shown alterations in protein abundance and its expression control in aged organisms, providing insights into the association of individual proteins with the aging process (David et al 2010;Mao et al 2010;Walther & Mann 2011;Reis-Rodrigues et al 2012;Janssens et al 2015;Vukoti et al 2015;Walther et al 2015;Narayan et al 2016). However, proteomics studies on asymmetric inheritance for individual damaged or old-age proteins likely to influence cellular aging have been limited.…”
Section: Introductionmentioning
confidence: 99%